The concept of digitization and research in the field of gert networks management of public sector projects and programs - Zasukha, Ihor (Transfer of innovative technologies, 2021)
The modern world space has long gone beyond the construction of the information society, because digital technologies are absorbing more and more spheres of public life, radically changing the forms and methods of their implementation. Therefore, most countries in the world focus on development in the direction of building a "digital economy", using all possible competitive advantages from its implementation. Ukraine is trying to keep up with the development of information technology in various areas of both public sector governance and public life. Some achievements have been made, but the systemic and synergistic effect on the country’s development has not been achieved, despite the significant potential of domestic IT specialists, who are among the top five IT outsourcers in the world. In my opinion, the use of digitalization in the field of governance in the public sector can be a significant impetus for digital transformation for the development of Ukraine’s competitive economy. Therefore, we need an analysis of theoretical and practical approaches to a detailed study of the features of digitalization in the public sector of Ukraine during its digital transformation and the development of proposals for their implementation, which became the topic of my research.